MG-108 Beyond the ACMG 56: Parental choices and initial results from a comprehensive whole genome sequencing-based search for predictive genomic variants in children. (4th December 2015) - Meyn, MStephen; Monfared, Nasim; Marshall, Christian R; Merico, Daniele; Stavropoulos, Dimitri J; Hayeems, Robin Z; Szego, Michael; Jobling, Rebekah; Girdea, Marta; Bader, Gary D; Brudno, Michael; Cohn, Ronald D; et al.
Abstract : Objective: The overall goal of the SickKids Genome Clinic is to pilot paediatric genomic medicine. To this end we have assessed parental interest in predictive secondary medically-actionable variants (MAVs) and used whole genome sequencing (WGS) to determine the frequency and nature of these MAVs in children. Design: The Genome Clinic conducts diagnostic WGS for 150+ children/year who are undergoing genetic evaluations. With parents' permission, we search children's genomes for predictive MAVs in 2800+ disease genes listed in the NIH Clinical Genomic Database. Results: Of 373 families approached to date, 56% agreed to participate. 58% of participants chose to learn their child's secondary adult-onset MAVs. Among these parents, 79% decided to learn their own status for these variants. Bioinformatics analysis of the first 100 patient genomes yielded 2957 candidate variants in 1132 genes ( 30 variants/genome). 70% of candidates were listed in HGMD. However, subsequent manual assessment rejected >90% of variants for dominant diseases listed in HGMD as disease causing due to inadequate evidence of pathogenicity. After manual assessment, 33/100 children had at least one reportable predictive MAV. 9 MAVs occurred in a 2013 ACMG-guideline reportable gene. Expanding our search 50 fold to include 2800+ disease genes yielded 29 additional reportable predictive MAVs. Return of predictive MAVs and assessment of their penetrance is underway. Conclusions: Parental opinions vary widely regarding return of predictive MAVs and comprehensive genomic analysis can yield predictive MAVs in 1/3 of children, with the number of reportable predictive MAVs constrained by disease prevalence and imperfect variant interpretation.